Community Empowerment in The Field of Education Through Sanggar Kegiatan Belajar in Surabaya City - Bayu Priambodo; Oktarizka Reviandani; Lia Nirawati (Future Science, 2022)
The phenomenon of children dropping out of school is a classic problem in Indonesia which does not only occur in remote areas where access to Education is still difficult but also occurs in big cities that are easy to access. Surabaya has a fairly large APBD where 20% of the APBD is allocated for education funds. However, there are still Surabaya residents whose children drop out of school because of financial problems. This study tries to see how the Surabaya City Government reduces the dropout rate through Sanggar Kegiatan Belajar. The research method used is qualitative, and the data search process uses interviews with the Education Authority and UPT Sanggar Kegiatan Belajar. The results showed that implementing Sanggar Kegiatan Belajar could reduce children dropping out of school due to cost problems. Sanggar Kegiatan Belajar is a non-formal education that is included in equality education so that those who enter the Sanggar Kegiatan Belajar will get free Education